Understanding How Trust Drives Saving Intention Toward Islamic Rural Banks - Ach Yasin; Imamuddin Imamuddin; Moch. Khoirul Anwar (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines how trust drives saving intention toward Islamic rural banks (BPRS) by investigating the roles of Islamic financial literacy, perceived security, and Islamic financial inclusion as antecedents of trust. Design/methodology/approach – A survey of 241 BPRS customers in Indonesia was analyzed using partial least squares structural equation modeling (PLS-SEM). Finding/Results – Islamic financial inclusion and Islamic financial literacy significantly enhance customer trust, while perceived security does not. Trust, in turn, strongly and positively influences saving intention. Trust fully mediates the effects of inclusion and literacy on saving intention. These findings provide practical implications for Islamic rural banks and regulators to enhance Islamic financial literacy and financial inclusion in strengthening public trust. Originality/Value – This study is among the early studies that position Islamic financial literacy and financial inclusion as determinants of trust in BPRS, while also demonstrating that perceived security is not always the primary determinant of trust. Therefore, this study fills a gap in the literature on customers’ saving behavior in BPRS, which remains underexplored from the customer perspective.